Examining the sources of police confidence when working with autistic individuals. Issue 3 (1st March 2022) - Love, Abigail M.A.; Railey, Kirsten S.; Jones, Colleen P.
Abstract : Purpose: Not only is the prevalence rate of autism spectrum disorder (ASD) rising, but there has been increased attention in the media focused on interactions between autistic individuals and police officers. Research suggests that police officers report concerns regarding how to appropriately support autistic individuals during interactions due to a lack of training opportunities or general knowledge of ASD. To contribute to this emerging research, the aim of the present study was to examine what makes police officers feel more or less confident when working with autistic individuals of all ages in the capacity of their job. Design/methodology/approach: In the present study, police officers' responses ( N = 317) to open-ended questions were analyzed using thematic analysis to understand what makes police officers feel more and less confident when interacting with someone with autism. Findings: Analysis yielded several major and minor thematic categories, which were combined into three major factors including (a) effective training, (b) malleable factors and (c) fixed factors. Originality/value: The findings of this study provide novel insight into police officer confidence to communicate and interact with autistic individuals. This research utilized the voices of police officers to identify areas of need and themes relating to officer confidence. The findings can be immediately used to inform research and practice and to improve relationships between first responders and the autistic community.